KEANEKARAGAMAN ARTHROPODA PADA TANAMAN JAGUNG (Zea mays L.) DENGAN PENGAPLIKASIAN INSEKTISIDA BOTANI DAN TANPA PENGAPLIKASIAN INSEKTISIDA BOTANI - Patabang, Nina K; Yunus, Moh.; Nasir, Burhanuddin (Fakultas Pertanian, Universitas Tadulako, 2024)
Arthropods, the largest taxon in the animal kingdom, serve as indicators of ecosystem balance. This study aimed to assess the diversity, evenness, and dominance of arthropods in corn (Zea mays L.) with and without botanical insecticide application. The research was conducted in Oloboju Village, Sigi Biromaru District, Central Sulawesi, from September to November 2022. The study utilized pitfall traps, light traps, and sweep nets to observe arthropods. The results indicated higher arthropod diversity without insecticide application: 4 classes, 14 orders, 44 families, 57 species, and 1,112 individuals, compared to 4 classes, 14 orders, 39 families, 49 species, and 891 individuals with insecticide. The diversity index and evenness index were higher without insecticide (3.04 and 0.75) than with insecticide (2.81 and 0.72). Both treatments had low dominance index values (0.10 and 0.12), suggesting no single species was dominant.